Pengaruh Gaya Hidup, Citra Merek Dan Kualitas Produk Terhadap Keputusan Pembelian Smartphone iPhone (Studi Kasus Mahasiswa di Kota Malang) - Alfiansyah, Zamzami Reza; Hidayati, Nur; Dianawati, Eris (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract This study aims to determine and analyze how much influence lifestyle, brand image, and product quality have on purchasing decisions for iPhone smartphones. Among Malang City students, the use of iPhones is very large not only as a means of communication but also as a symbol of status and lifestyle. The population in this study were students who used iphone smartphones in Malang City. The data collection method in this study used a questionnaire with the number of samples determined using the Hair et al formula and the results obtained were 119 respondents. The data testing techniques used in this study include validity test, reliability test, normality test, classical assumption test, multiple linear regression analysis test, f test, t test and determination coefficient test (R2). The results of this study simultaneously show that the influence of lifestyle, brand image and product quality has a positive and significant effect on purchasing decisions. Partially, Lifestyle, Brand Image and Product Quality have a significant effect on iPhone Purchasing Decisions. Keywords: Lifestyle, Brand Image, Product Quality and Usage Decision